2014
DOI: 10.5901/mjss.2014.v5n27p416
|View full text |Cite
|
Sign up to set email alerts
|

Technical Efficiency and Determinants of Maize Production by Smallholder Farmers in the Moneragala District of Sri Lanka

Abstract: Maze (Zea mays L.) is the second most important cereal crop after rice produced in Sri

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Irrigation dummy variable was significant and positive as expected, suggesting that potato producers who used irrigation water were more technically efficient than their counterparts. This finding is similar to that of Anang et al (2016) and Esham (2014) who reasoned out that access to irrigation enables farmers to maximise the use of other inputs such as fertiliser due to the availability of water throughout the farming season. Alam et al (2012b) reported that irrigation system has a positive and significant impact on technical efficiency of potato production in Pakistan.…”
Section: Discussionsupporting
confidence: 90%
“…Irrigation dummy variable was significant and positive as expected, suggesting that potato producers who used irrigation water were more technically efficient than their counterparts. This finding is similar to that of Anang et al (2016) and Esham (2014) who reasoned out that access to irrigation enables farmers to maximise the use of other inputs such as fertiliser due to the availability of water throughout the farming season. Alam et al (2012b) reported that irrigation system has a positive and significant impact on technical efficiency of potato production in Pakistan.…”
Section: Discussionsupporting
confidence: 90%
“…Apart from paddy, of the key crops considered in the present study, i.e. maize, potato, soybean, chilli and B-onion, the highest mean TE was recorded in B-onion (0.83±0.15) whereas the lowest was recorded in maize (0.703±0.09) and in soybean (0.705±0.13) [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. The TE of chilli cultivation was 0.78 with the greatest variability (standard error of mean [SEM] 0.19) among those crops, that signifies the unpredictable nature of the chilli cultivation [27][28][29][30][31].…”
Section: Resultsmentioning
confidence: 99%
“…Socioeconomic factors that affect technical efficiency in research were farming experience, number of family dependents, frequency of counseling, and research. Some socioeconomic factors that can affect technical efficiency are the age of farmers, education level, labor in the family, farm size, sex, gender, experience, microcredit, training, extension (see Villano 2006;Otitoju & Arene 2010;Akram et al 2013;Ligeon 2013;Tung 2013;Esham 2014;Majumder et al 2016). Technological factors in the study by Esham (2014) were dummy purchases of hybrid seeds and irrigation land ownership.…”
Section: Analysis Of Technical Efficiency and Inefficiencymentioning
confidence: 99%